1987
DOI: 10.1111/j.1365-246x.1987.tb01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism and isotopic age data from Upper Cretaceous igneous rocks of W. Portugal; geological correlation and plate tectonic aspects

Abstract: Palaeomagnetic results and K-Ar age data for the Sintra and Sines intrusive complexes (W. Portugal), and further details on the palaeomagnetic structure of the Lisbon volcanics are reported. The Sintra complex consists of two main intrusive phases having been emplaced in the Upper Cretaceous at around 90 Ma and 75 Ma respectively. The radiometric results show that the Sines complex formed concurrently with the second Sintra magmatism. The early (main) Sintra pluton has a characteristic magnetization of D=358',… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Other poles were excluded because of their inconsistent position and shallow inclination (Figure 10a). These include the Sines, Cabo da Roca, Sintra Pluton (numbers 5, 6 and 9 [ Storetvedt et al , 1987]), and Hostal Nou poles (number 27 [ Gong et al , 2008a]). Finally, the Organyà basin (number 10 [ Dinarès‐Turell and Garcia‐Senz , 2000]) and Lisbon area sediments (number 13 [ Galdeano et al , 1989]) were not considered because of inconsistent pole positions and large α 95 values (Table 2 and Figure 10a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other poles were excluded because of their inconsistent position and shallow inclination (Figure 10a). These include the Sines, Cabo da Roca, Sintra Pluton (numbers 5, 6 and 9 [ Storetvedt et al , 1987]), and Hostal Nou poles (number 27 [ Gong et al , 2008a]). Finally, the Organyà basin (number 10 [ Dinarès‐Turell and Garcia‐Senz , 2000]) and Lisbon area sediments (number 13 [ Galdeano et al , 1989]) were not considered because of inconsistent pole positions and large α 95 values (Table 2 and Figure 10a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the Lusitanian and Algarve Basins have allowed the identification of the following three magmatic pulses: (1) Tholeiitic volcanism of earliest Jurassic age as the northernmost manifestation of the Central Atlantic Magmatic Province [ Martins et al , 2008; Verati et al , 2007]; (2) A magmatic pulse of alkaline transitional composition occurs as scattered small‐scale plugs and sills of Late Jurassic age [ Grange et al , 2008; Martins , 1991]; (3) the Late Cretaceous alkaline magmatic event comprising the igneous intrusive complexes of Sintra (84–79 Ma) [ Macintyre and Berger , 1982; Miranda et al , 2009; Storetvedt et al , 1987], Sines (75 Ma) [ Miranda et al , 2009], Monchique (72 Ma) [ Bernard‐Griffiths et al , 1997; Miranda et al , 2009; Rock , 1982], and the Lisbon volcanic complex (73 Ma) [ Ferreira and Macedo , 1979] (Figure 1a). The PI and FF sills are two of several scattered sub‐volcanic intrusions that belong to this third event [ Miranda , 2010; Miranda et al , 2009], and were emplaced into Lower Cretaceous shallow marine sediments.…”
Section: Geological Settingsmentioning
confidence: 99%
“…Results from igneous rocks seemed to suggest complicated rotations, both in the CCW and CW sense, before Iberia became eventually attached to Europe (Storetvedt et al, 1987(Storetvedt et al, , 1990. Paleomagnetic data from Jurassic-Cretaceous sediments (Galdeano et al, 1989;Moreau et al, 1997) indicated only CCW rotations during the Cretaceous.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, important igneous activity is known during Turonian-Eocene (Lisbon volcanics) in the Lusitanian basin, and there are intrusions of moderate sizes in Algarve, the "Salema intrusions" (petrological affinity connects them to the Monchique complex) which cut Triassic and Jurassic sediments. Radiometric data for the massifs are also available, which are Rb-Sr whole rock isochron, Rb-Sr model, and K/Ar ages (Bonhomme et al, 1961;Mendes, 1968;Canilho, 1971;Rock, 1976;Abranches and Canilho, 1981;Canilho and Abranches, 1982;MacIntyre and Berger, 1982;Storetvedt et al, 1987;Storetvedt et al, 1990). For the Lisbon basalts the last two (Ferreira and Macedo, 1979;Alves et al, 1980), for the Salema intrusions, only the last (Storetvedt et al, 1990) method was used.…”
Section: Geological Frameworkmentioning
confidence: 98%
“…It crops out in the central-western part of Portugal and has an elliptical shape of approximately 16 km 9 6 km aligned E-W. It is composed of granites (79.2 ± 0.8 Ma, U-Pb zircon geochronology Miranda et al 2009) that are intruded by a suite of gabbro-diorite-syenite and associated breccias (74.9 ± 1.0 to 78.3 ± 1.9 Ma, K-Ar in whole rock syenite and gabbro Storetvedt et al 1987), in the core of the structure. The SIC was uplifted by tectonic inversion during the Miocene (Kullberg et al 2006) along an E-W thrust zone located further north.…”
Section: Geological Description Of the Area And Available Datamentioning
confidence: 99%